COST-EFFECTIVE AND HIGH-PERFORMANCE DYE-SENSITIZED SOLAR CELLS USING POLYMER-BASED COUNTER ELECTRODES - Bukari, Sherif Dei (School of Sciences and Humanities, 2023)
Solar energy has proven to be the most promising solution to the current and future world energy and environmental challenges. One of the most promising technologies to harvest solar energy is the dye-sensitized solar cell (DSSC) due to its eco-friendliness, affordability, high efficiency, good durability, and simple manufacturing processes. An expensive platinum electrode is one of the major limitations of DSSCs. Here we fabricate a cheaper and more effective counter electrode based on Poly(3,4-ethylene dioxythiophene) and N-alkyl carbazole derivatives (N-butyl-, N-hexyl-, and N-octyl carbazole) copolymers (PEDOT-CO-RCbz) as better substitutes for the traditional platinum counter electrode via a simple electrochemical deposition method. The fabricated PEDOT and PEDOT-CO-RCbz counter electrodes have a highly porous sponge-like morphology with lower charge-transfer resistance and higher electrocatalytic activity for catalyzing the iodine/triiodide redox reaction than the classical Pt electrodes. The DSSCs with PEDOT-CO-RCbz counter electrodes all have better power conversion efficiency (the highest being 8.88%) than the DSSC with only PEDOT (7.9%) and Pt (~7.6%) counter electrodes. The superior photoelectric characteristics, a straightforward preparation process, and a low cost make PEDOT-CO-RCbz counter electrodes promising substitutes for DSSCs.
Keywords: Type of access: Open Access; dye-sensitized solar cells; polymer-based counter electrodes